The Relationship of Age and Gender with Disaster Preparedness among Emergency Nurses - Su’aida, Desi Holifatus; Fujianti, Mery Eka Yaya; Istibsaroh, Faridatul (LPPM Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Disasters are events that threaten life. It is likely that disaster events will increase globally as a result of climate change. Therefore, there is a need for a strategy to overcome disasters, namely by carrying out disaster management. Nurses have an important role in disaster management, namely by implementing disaster preparedness. Disaster preparedness among nurses is influenced by many factors including age and gender. The aim of this research is to determine the relationship between age and gender and disaster preparedness among emergency nurses at the Sumenep Regency regional health center. The research design is Cross-Sectional. The population in this study was Emergency Nurses at the Sumenep Regency Regional Health Center which involved 7 health centers with a population of 96 nurses. The sampling technique used was total sampling with the independent variables namely gender and age, while the dependent variable was disaster preparedness in emergency nurses. Data collection was carried out using a questionnaire which was filled out directly by nurses working in the Emergency Room. At the beginning, before filling out the questionnaire, the researcher first explained the aims and objectives of the research. Once the respondent understands and is willing to participate, the respondent can immediately fill out the questionnaire. Respondent characteristics and disaster preparedness were analyzed using descriptive statistics, while to determine the relationship between respondent characteristics and disaster preparedness in emergency nurses using the Spearman Rank test. The significance level for analysis was set at 0.05. Results: The results of the study showed that there was a relationship between gender and age and disaster preparedness in emergency nurses (p value <0.05). Conclusion: the older a person gets, the higher their ability to think and work, where women tend to work carefully while men prioritize the end result.